Influência de agregados a base de ZrO2 e MgAl2O4-ZrO2 nas propriedades de concretos refratários - Ramos, Lucas Jose de (Universidade Federal de São Carlos, 2024)
Refractory linings are essential materials in foundational industries due to their ability to withstand harsh operating conditions without losing their functional capabilities. These ceramics represent a significant portion of production costs in sectors such as steelmaking, petrochemicals, and non-ferrous metallurgy. Consequently, enhancing the quality and extending the lifespan of these materials has become a top priority amid industry competition and the need to reduce costs. Alumina refractory castables are widely used for their excellent mechanical properties at high temperatures. However, when exposed to environments with abrupt temperature variations, they are susceptible to thermal shock damage. In this context, the combination and/or substitution of alumina aggregates with other types of oxides, such as partially stabilized zirconia and zirconia-spinel (MgAl2O4), may be alternatives with the potential to develop refractories with increased resistance to cracking due to the toughening mechanisms of these components. This study aimed to analyze the effect of adding ZrO2 and MgAl2O4-ZrO2 aggregates to alumina castables containing cement. Initially, the physico-chemical and mineralogical characteristics of the chosen aggregates were analyzed. Subsequently, three refractory formulations were developed and characterized through tests including flowability, three-point bending, elastic modulus, linear dimensional variation, apparent density, apparent porosity, and thermal shock resistance. The results indicated that the composition containing zirconia-spinel aggregates showed properties similar to the reference castable. However, the incorporation of zirconia aggregates resulted in a decrease in the mechanical properties of the prepared composition, possibly due to differences in thermal expansion coefficients at the aggregate-matrix interface. Nevertheless, it was observed that refractories containing ZEC and ZEFZ aggregates performed well when subjected to thermal shock tests, as evidenced by the low percentage drop in the elastic modulus of these materials.
Influence of ZrO2 and MgAl2O4-ZrO2-based aggregates on the properties of refractory castables
Keywords: Zircônia; Agregado; Espinélio; Choque térmico; Concreto refratário; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS